Tinjauan Yuridis Terhadap Tindak Pidana Perkosaan Dalam Perspektif Hak Asasi Manusia - Kadek Dwi Novitasari; Ida Ayu Putu Widiati; I Nengah Laba (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract—Rape crime is the most common case in Indonesia. Rape is a crime that is very cruel, immoral, despicable and violates the norm where the victims are women both adults and minors. Rape violates Human Rights especially for women. The formulation of the problem raised is how to protect the law of women who are victims of rape in the perspective of human rights and how criminal sanctions are applied to perpetrators of rape crimes. This type of research is a research with a legal and conceptual problem approach. The results of this study indicate that legal protection that can be given to women who are victims of acts of sexual violence / harassment is stipulated in Article 285 of the Criminal Code and Law No. 13 of 2006 specifically in Article 5, Article 8, and Article 9 which are generally in the form of protection and rights of witnesses and victims. Victims of sexual violence have rights that must be enforced, hurt, suffering, fear, and various kinds of adverse effects that befall him after rape and need serious attention. While criminal sanctions against perpetrators of criminal acts of rape have been regulated in general in Article 285 of the Criminal Code which faces a sentence of twelve years in prison.